Penguatan Peran Kader Keswa dalam Pertolongan Pertama Kegawatdaruratan Psikiatri: Implementasi dan Hasil di Puskesmas Bantur - Priasmoro, Dian Pitaloka; Asri, Yuni; Soebagijono, Soebagijono (Kolaborasi: Jurnal Pengabdian Masyarakat, 2024)
Introduction: This community service activity aims to enhance the capabilities of mental health cadres (Keswa) in providing first aid for psychiatric emergencies at Puskesmas Bantur. Objective: A total of 25 cadres participated in the training, which covered both theoretical and practical aspects of handling psychiatric emergency situations. Method: The training began with lectures on the fundamentals of psychiatric emergencies and first aid techniques. Results: Participants then engaged in case simulations to apply their knowledge in real-life scenarios. Discussions and Q&A sessions were held to deepen understanding and address participants' questions. The evaluation results showed a significant improvement in the cadres' knowledge and skills. Conclusion: Prior to the training, many cadres felt uncertain about managing psychiatric emergencies. After the training, they demonstrated increased confidence and improved ability to apply first aid techniques. This activity is expected to enhance the effectiveness of cadres in providing field support and strengthen their role within the community health system.